SOME ASPECTS OF THE IMPACT OF MARKET INFRASTRUCTURES ON SMALL BUSINESS ENTITIES - Saidullaeva Saodat Abdumajitovna; Nurullaeva Shakhnoza Tokhtasinovna (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
This article provides insights and considerations on some aspects of the impact of market infrastructures on small business entities.